PENGARUH TINGKAT PENDIDIKAN WANITA DAN PENDAPATAN PER KAPITA TERHADAP GIZI BURUK BALITA DI PROVINSI KALIMANTAN BARAT - admin, NICKO ARDINATA B01112054 (Jurnal Pembangunan dan Pemerataan, 2016)
research aims to exaims and analyze the effect of women’s educationlevel and per-capita income on malnourished children under five years old inWest Kalimantan Province. This study used an explanatory method (explanatoryresearch) and the type of data used was panel data (time series and crosssection).Instruments of data collection used secondary data from the institution’sconcerned. The technique for data analysis in this study used multiple linearanalysis with a data procsseing program of Eviews 8. This research used 14regencies and a 5-year time series so 70 observations were obtained.The result of hypothesis testing showed that the variable of women’seducation level had a negative and significant effect on malnourihed childrenunder five with a significance level of 0.0000 < 0.05. The variable of per-capitaincome had a negative and insignificant effect on malnourihed children under fivewith a significance level of 0.2062 > 0.05.Kewords: Women’s Education Level, Per-Capita Income And MalnourishedChildren Under Five.